Sex and sexuality in African traditional religions: exploring trends among the Shona people of Zimbabwe - Sipeyiye, Macloud; Konyana, Elias G. (African institute for Culture, Peace, Dialogue & Tolerance Studies, 2019)
Sexuality is a closely guarded and secretive subject in many religions in general and African Traditional religions in particular. Public discussion of sexuality is socially discouraged, especially between adults and youth. As a result, secrecy surrounds the subject of sexuality in African Traditional Religions. However, African Traditional Religions have been overwhelmed by many social changes that prompted us to look again at their position on sexuality. Sexuality can no longer afford the cover of secrecy in the wake of social changes engendered by HIV and AIDS, gender and human rights debates among other things. These factors challenge the deeply rooted and dearly held beliefs and practices regarding sexuality. The Chapter argues that the religio-cultural beliefs and practices regarding sexuality need updating to have relevance to the current life circumstances of the adherents. Using, but not limited to the Shona Traditional Religion, we seek to explore the trends on sexuality in African Traditional Religions. Using a socio-historical analysis we seek to examine the changing perceptions on sexuality in different social and historical contexts. African Feminist ethic provides the theoretical grounding the rationale being that the discourse of sexuality has largely centred on woman sexuality and hegemonic masculinity. We found out that African Traditional Religions are shifting their position on sexuality. The issue of sexuality is fast becoming a public subject.